Breeding habitat selection in the great grey shirke Lanius excubitor - the importance of meadows and spring crops - Tryjanowski, Piotr; Hromada, Martin (1969– ); Antczak, Marcin (Muzeum i Instytut Zoologii PAN, 1999)
Habitat composition of breeding territories, habitat use during foraging, and nest-site selection of the Great Grey Shrike Lanius excubitor were examined in western Poland during years 1998-1999. Meadows and spring crops occurred within territories more frequently than expected by their availability. Habitat utilisation during foraging was significantly non-random and shrikes appeared to prefer low vegetation. All of 27 nests were located along tree lines and edges of small woodlots (maximum 7 m), and neither deciduous nor coniferous trees were preferred (78% and 22%, respectively). Preferred habitats of Great Grey Shrikes are relatively uncommon in modern agricultural landscape. Lack of suitable habitats in intensively used farmland may be the most important reasons for shrike population decline over Europe. Wielkopolska region offers good breeding habitats and this species has more dense and stable population over here, than in other parts of Europe.
Bibliogr. s. 62
S. [59]-63 : il. ; 27 cm
Streszcz. pol. Nazwy taksonów także w jęz. łac.
Keywords: Srokosz -- biologia lęgowa -- Polska -- Wielkopolska (region) [KABA]; wybiórczość siedliskowa; zboża jare; łąki; dzierzbowate; ptaki; Lanius excubitor; Laniidae; Aves; 1998-99